Usia Menarche dari Sudut Pandang Konsumsi Fastfood dan Paparan Media Porno - Ronasari Mahaji Putri; Novitadewi Novitadewi; Neni Maemunah (Universitas Baiturrahim, 2020)
Many young women experience accelerated menarche age compared to previous years. The high consumption of fast food and exposure to pornographic media is one of the factors that is suspected to influence the age of menarche acceleration. The purpose of this study was to determine the relationship of junk food consumption, media exposure to the age of menarche in young women. The research design uses cross-sectional. The population is all VII grade students of SMPN 26 Malang, with a sample of 90 students obtained by using simple random sample technique. The instrument uses a questionnaire and a checklist sheet. Data analysis using Fisher's exact test. The results of the study revealed that the majority of respondents consumed fast food in the low category of 82 people (91.1%). Most of the children experienced low exposure to pornographic media, namely 80 people (88.9%). Statistical tests show that there is no relationship between junk food consumption (p value = 0.416), and exposure to pornographic media (p value = 0.270) with the age of menarche in SMPN 26 Malang students. It is recommended for further researchers to explore the determinants of the acceleration of the age of menarche in adolescent girls, as well as the delay in the age of menarche, further research needs to be done